Consumers shopping preferences for retail format choice between modern and traditional retails in Malaysia - Terano, Rika; Yahya, Rafidah; Mohamed, Zainal Abidin; Saimin, Sahbani (Routledge, 2014)
The retail landscape in Malaysia is transforming from a traditional to a modern retail format. The large retailers are increasing their dominance over small shops in the country by offering their customers a wide stock of fresh food products. The small shops are still surviving, although with difficulty, and they continue to provide a choice of shopping venue. The objective of this study is to show the advantages of both the modern and traditional retailers that are available to Malaysian consumers and to investigate what determines consumers’ shopping preferences for their retail format. A structured questionnaire was constructed to gather shopping preferences from 650 respondents in Selangor. Descriptive analysis, factor analysis, and binary logit model were used to analyze the data. The results show that sociodemographic variables such as age, education, being accompanied by children while shopping, and family size as well as packaging, store environment, and price of products have influence on retail format choice.